Target Group Behavior for Policy Performance Impact: Study on Poverty Reduction Implementation in Makassar, Indonesia - Anirwan, Anirwan; Ibrahim, Muhammad Akmal; Hasniati, Hasniati; Lambali, Suryadi (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
The implementation of poverty reduction policies in Makassar City is still reaping many problems. Various poverty reduction programs launched by the government have not been able to eradicate poverty effectively. In the implementation of these various poverty reduction programs, the response of the target group tends to be negative, causing fragmentation at the level of implementation. Therefore, this study aims to identify and analyze the process of implementing poverty reduction policies in Makassar City from the perspective of group behavior. The research method used is a qualitative method with data collection techniques through in-depth interviews, field observations, and review of poverty documents. The research data were analyzed by qualitative analysis. The results show that the community is basically very responsive to the existence of poverty reduction policies in the form of multi-purpose social security assistance distributed by the Makassar City Social Service because some of them feel helped by the assistance, but some also feel that the policies are not well targeted due to incomplete data collection. equitable and fair. The inaccuracy of policy targets (assistance for beneficiaries) for the poor causes social jealousy in the community which has an impact on street level publicity and policy performance so that it does not significantly reduce poverty in Makassar City.